Attachment Behaviour, Attachment Representations, and Symptoms of Reactive Attachment Disorder and Disinhibited Social Engagement Disorder in Foster Children With Different Preplacement Experiences - Jorjadze, Nino; Bovenschen, Ina; Spangler, Gottfried (Developmental Child Welfare, 2023)
Foster care offers children a safe family environment and is effective in buffering the negative effects of early adversity. Specifically, foster care has been found to facilitate secure attachment to foster parents. However, there are limited data on attachment development in children entering foster care after the first year of life. In this study, we examined attachment behaviour and representations as well as symptoms of reactive attachment disorder (RAD) and disinhibited social engagement disorder (DSED) in 3–6 year-old foster children. We studied two subgroups of foster children with different preplacement experiences (Group 1: children entering foster care after living in institutions; Group 2: children entering foster care after living with their biological families) and compared them with a community sample. The results revealed that children in both foster care groups showed significantly lower attachment security at the behavioural level, higher hyperactivation and disorganization at the representational level, and significantly more symptoms of RAD and DSED than the children in the control group. Analyses did not indicate significant differences between the foster care groups. Moreover, no significant associations were found between attachment-related variables and preplacement experiences. This may be an indication that in long-term foster care, the quality of foster care becomes the major factor affecting a child’s attachment development. Thus, foster parents need supportive services and interventions with a focus on attachment development.
CRIS-Team Scopus Importer:2024-12-16
Keywords: attachment; early adversity; foster children; institutionalization; reactive attachment disorder and disinhibited social engagement disorder symptoms